Impact of Entrepreneurship Orientation, Innovation, Market Orientation and Total Quality Management on SME Performance - Raja Adri Satriawan Surya; Ulfa Afifah; Mayla Khoiriyah; Vera Oktari (International Journal of Organizational Behavior and Policy, 2022)
Small and Medium Enterprises (SMEs) have had a very good impact on economic development in Indonesia. In addition, the presence of SMEs also brings many benefits to the welfare of the community, one of which is by absorbing the workforce so that it can reduce the number of unemployment figures. To see the success or failure of a business can be seen from the measurement of performance. Measuring the performance of a business is a very important thing, because by measuring the performance of the company can find out how much reward or salary will be given to employees. This study aims to examine whether entrepreneurial orientation, innovation, market orientation and total quality management affect the performance of SMEs. This study uses primary data with questionnaires as research instruments. The population in this study was 1,599 SMEs located in Kuantan Singingi Regency. The number of samples used was 115 with a purposive sampling method. The test results show that the independent variable entrepreneurial orientation, innovation, market orientation affect the performance of SMEs, while the independent variable total quality management has no influence on the performance of SMEs. This research is expected to be a material consideration for making changes in business for business entities and organizations so that business performance can improve.